Factors affecting the choice of Asian MBA program among overseas students. - Lee, Lee Chen. (2008)
Seeks to understand the motivational drivers for the overseas students’ choice of their postgraduate school in Asia through surveys conducted in Hong Kong University of Science and Technology and Nanyang Business School.